1983
DOI: 10.1016/0014-5793(83)80742-x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential enhancement of myoblast differentiation by insulin‐like growth factors (IGF I and IGF II) in primary cultures of chicken embryonic cells

Abstract: Cells prepared from the body walls of chicken embryos were plated in the absence of serum. Insulin‐like growth factors (IGFs) barely stimulated cell replication, but preferentially enhanced the differentiation of muscle cells. Myoblast fusion was favoured in the presence of IGF (or insulin). Concomitantly, acetylcholinesterase activity increased. IGF I and IGF II were equipotent and active in low physiological concentrations, in contrast to insulin, which was known for a long time to exert such effects at phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(49 citation statements)
references
References 9 publications
4
44
0
1
Order By: Relevance
“…Because of the cross-reactivities to their receptors, these studies do not demonstrate whether insulin is acting on the CFU-E through its own receptors or through IGF-I receptors (33,34). It has been accepted that the effects of IGF-I may be initiated by insulin, but a concentration of insulin of about 20-100 times greater than that of IGF-I is necessary in most systems (20,21,(35)(36)(37). This would indicate that large concentrations of insulin may be acting on the CFU-E through interaction with IGF-I receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the cross-reactivities to their receptors, these studies do not demonstrate whether insulin is acting on the CFU-E through its own receptors or through IGF-I receptors (33,34). It has been accepted that the effects of IGF-I may be initiated by insulin, but a concentration of insulin of about 20-100 times greater than that of IGF-I is necessary in most systems (20,21,(35)(36)(37). This would indicate that large concentrations of insulin may be acting on the CFU-E through interaction with IGF-I receptors.…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study, using avian (turkey) satellite cells, has shown that IGF-2 mRNA was expressed at higher levels during the proliferative phase, followed by a marginal reduction during differentiation (Ernst et al, 1996). Like IGF-1, IGF-2 is also a potent regulator of chicken muscle cell proliferation (Duclos et al, 1991) and differentiation (Schmid et al, 1983). However, unlike IGF-1, IGF-2 administration does not promote lean growth in young chicken (Tomas et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, it stimulates the proliferation of a wide variety of cultured cells that are primarily of mesodermal origin (3)(4)(5). In addition, it can cause some cells to differentiate including chondrocytes (6), myoblasts (7), osteoblasts (8) and erythroid precursors (9). In vivo, IGF-I regulates postnatal skeletal growth (5,10).…”
Section: Introductionmentioning
confidence: 99%